Human–Monkey Conflict and Community Responses in Bheemdatta and Bedkot Municipalities, Kanchanpur, Nepal - Joshi, Manmati; Bista, Mahadev; Awasthi, Balram (Api Journal of Science, 2025)
Human-monkey conflict is increasing in most parts of Nepal due to rapid land-use change, habitat loss, and expanding human settlements. This study assessed the patterns, drivers, and community responses to HMC in Bheemdatta and Bedkot Municipalities of Kanchanpur District. The types of conflict, perceived drivers, local mitigation strategies, and community attitudes towards monkeys were documented through household surveys (160 households (80 per municipality), key informant interviews and field observations. Most of the respondents reported frequent crop damage, food theft, property destruction, and safety concerns. Our results indicated that habitat degradation and food scarcity are the major drivers of HMC. Bedkot, characterized by forest-adjacent farmlands, reported higher crop losses and more frequent encounters, while Bheemdatta experienced predominantly urban-related incidents such as food snatching and household intrusion. Communities primarily relied on reactive measures (stone-throwing, guarding), which were often ineffective. Despite economic losses, cultural and religious values promoted tolerance toward monkeys, although expectations from local authorities varied across municipalities. The present study recommends community-based mitigation, improved land-use planning, and future integration of ecological and spatial data for hotspot identification to guide management strategies.